Commutators of Fractional Integral with Variable Kernel on Variable Exponent Herz and Lebesgue Spaces - Afif Abdalmonem; Omer Abdalrhman; Shuangping Tao (International Journal of Mathematics And its Applications, 2016)
In this paper, we study the boundedness for commutators of the fractional integral with variable kernel on Lebesgue spaecs with variable exponent. Also, we study the boundedness of the fractional integral operator and their commutator generated by BMO function is obtained on those Herz spaces with two variable exponent $p(·), q(·)$.